OP39 Safety of ustekinumab in IBD: Final pooled long-term safety analysis through 5 years in CD and 4 years in UC. (30th January 2023) - Ghosh, S; Feagan, B; Ott, E; Gasink, C; Marano, C; Miao, Y; Sandborn, W; Danese, S; Abreu, M; Sands, B
Abstract: Background: Long-term efficacy of ustekinumab (UST) has been reported in Crohn's disease (CD) through 5 years (yrs) 1 and in ulcerative colitis (UC) through 4 yrs. 2 A previous pooled analysis of long-term safety data reported a favorable UST safety treatment profile for inflammatory bowel disease (IBD). 3 Here, we present results of the final cumulative analysis of long-term safety data from UST studies through up to 5 yrs in CD and 4 yrs in UC. Methods: Data from 6 phase 2/3 UST IBD studies were pooled. In phase 3, patients (pts) received a single IV placebo (PBO) or UST (130mg or ~6mg/kg) induction dose followed by SC maintenance doses of PBO or UST (90mg q8w or q12w). Concomitant immunomodulators and corticosteroids were permitted. All pts who received ≥1 dose of UST were included. Safety outcomes are summarized and presented using number of events per 100 patient-years (PY) of follow-up and corresponding 95% confidence interval (CI). Results: In this final pooled UST IBD safety data, 2575 pts were treated with UST with 4826 PYs of follow-up. Rates of key safety events, including MACE and malignancies, were similar between PBO and UST or not higher for UST (Table 1). The most frequently occurring adverse events (AEs) in either group (excluding diseases under study) were headache (PBO 16.66 vs. UST 11.60), arthralgia (PBO 15.91 vs. UST 11.23), abdominal pain (PBO 13.79 vs. UST 9.86), nausea (PBO 11.35 vs. UST 7.13), and pyrexia (PBO 11.35 vs. UST 5.91); infections were nasopharyngitis (PBO 17.82 vs UST 19.10) and upper respiratory tract infection (PBO 11.78 vs UST 9.80). The most frequently reported serious infections of anal abscess, pneumonia, cellulitis, and abdominal abscess were no higher in the UST group than PBO, except gastroenteritis (PBO 0.11 vs UST 0.25). No lymphomas were reported. Nine deaths were reported in UST-treated pts (0.00 [0.00, 0.32] PBO vs. 0.19 [0.09, 0.35] UST), 6 in CD and 3 in UC (all considered unrelated to study agent). Conclusion: The final compilation of cumulative UST IBD safety data through 5 yrs in CD and 4 yrs in UC showed a safety profile that continued to be favorable and supports the well-established UST safety experience across all approved indications. References: 1. Sandborn WJ, et al. Five-Year Efficacy and Safety of Ustekinumab Treatment in Crohn's Disease: The IM-UNITI Trial. Clin Gastroenterol Hepatol. 2022;20(3):578-590.e4. 2. Afif W, et al. Efficacy and Safety of Ustekinumab for Ulcerative Colitis Through 4 Years: Final Results from The UNIFI Long-term Extension. UEGW 2023. 3. Sandborn WJ, et al. 129 Safety of Ustekinumab In IBD: Pooled Safety Analysis through 5 years in CD and 2 Years in UC. Gastroenterology. 2021;Supplement:S-35-S-36.